Race to Quality: A Study of Tasar Silkworm Cocoon Traits - Kumar, Ashok; Nadaf, Hasansab; Yadav, Priyanka; Sahu, Hemlal; Selvakumar, T.; Periyasamy, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This research work investigates the post-cocoon parameters of three Tasar silkworm races: Daba Bivoltine (DBV), Daba Trivoltine (DTV) and BDR-10, reared during the second crop, to enhance understanding of their qualitative and quantitative traits for commercial sericulture. Conducted at the Silk Technical Service Center (STSC) of Central Silk Technological Research Institute (CSTRI), Central Silk Board (CSB) in Bilaspur, Chhattisgarh, the study measured various parameters, including peduncle length, weight, thickness, cocoon color, shape, weight, shell weight, shell ratio, filament length, non-broken filament length (NBFL), filament denier, raw silk recovery, reelability, boil-off loss and the number of cocoons required to produce 1 kg of raw silk. The results revealed that BDR-10 exhibited the highest cocoon weight, reelability and raw silk recovery, making it the most productive race, while DBV showed superior filament length, shell weight and denier, providing a balance between productivity and quality. Although DTV demonstrated lower performance in some parameters, it exhibited the highest shell ratio and filament denier, indicating its potential for specific applications requiring thicker filaments. The study concludes that BDR-10 is the most promising race for maximizing silk yield and quality, DBV offers a balanced option, and DTV can still be utilized for commercial reeling with appropriate precautions.